2016
DOI: 10.1038/cmi.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational regulation of inflammasomes

Abstract: Inflammasomes play essential roles in immune protection against microbial infections. However, excessive inflammation is implicated in various human diseases, including autoinflammatory syndromes, diabetes, multiple sclerosis, cardiovascular disorders and neurodegenerative diseases. Therefore, precise regulation of inflammasome activities is critical for adequate immune protection while limiting collateral tissue damage. In this review, we focus on the emerging roles of post-translational modifications (PTMs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 200 publications
(250 reference statements)
7
141
1
1
Order By: Relevance
“…[42][43][44] It was also observed that 3-MA particularly abolished AIM2 inhibition by RGFP966 in our study, indicating plausible autophagosome regulations between RGFP966 and AIM2. [42][43][44] It was also observed that 3-MA particularly abolished AIM2 inhibition by RGFP966 in our study, indicating plausible autophagosome regulations between RGFP966 and AIM2.…”
Section: Discussionsupporting
confidence: 82%
“…[42][43][44] It was also observed that 3-MA particularly abolished AIM2 inhibition by RGFP966 in our study, indicating plausible autophagosome regulations between RGFP966 and AIM2. [42][43][44] It was also observed that 3-MA particularly abolished AIM2 inhibition by RGFP966 in our study, indicating plausible autophagosome regulations between RGFP966 and AIM2.…”
Section: Discussionsupporting
confidence: 82%
“…The recruitment of this machinery to AIM2 leads to AIM2 degradation via selective autophagy . These findings demonstrate that post‐translational modifications contribute to inflammasomes regulation and may be key at regulating the intensity and duration of the inflammatory responses …”
Section: Regulation Of Aim2mentioning
confidence: 78%
“…6 To date, several inflammasomes have been described, including NLRP1, NLRC4, AIM2, and NLRP3 inflammasome, and the NLRP3 inflammasome is the most characterized one. 9,10 It is reported that NLRP3 inflammasome can be activated by many different stimuli including PAMPs and DAMPs. In addition, a newly identified protein NEK7 (NIMA-related kinase 7), which can directly bind to NLRP3 protein, is also thought to be the component of NLRP3 inflammasome.…”
Section: Introductionmentioning
confidence: 99%